Nuevos registros y observaciones de aves para las provincias de Tucumán y Santiago del Estero - Capllonch, Patricia; Ortiz, Diego; Ruiz, Claudio; Lobo Allende, Rebeca (Nuestras Aves, 2005)
Este artículo no cuenta con un resumen.